Assessing the Implementation of Republic Act 9184 in the Procurement Stages of Fishery Post-Harvest Infrastructure Facilities in the Philippines - Dante, John Ray; Bernabe , Guillermo (Journal of Interdisciplinary Perspectives, 2024)
In line with the Philippine government's thrust to reduce post-harvest fish losses, properly implementing Republic Act (RA) 9184 is important for ensuring timely and systematic procurement of government fishery post-harvest infrastructure facilities. This quantitative, descriptive-comparative study analyzes the current implementation of RA 9184 in the procurement of said facilities, focusing on procurement stages: pre-procurement (procurement planning), actual procurement, and post-procurement (procurement monitoring). It also examines differences in the respondents' assessment of procurement stages when grouped according to demographic and professional profiles. The respondents from this study included 70 procurement personnel from fishery-related government agencies, selected through purposive sampling. Survey questionnaires, validated by experts, were administered and collected online via Google Forms and analyzed using descriptive and nonparametric statistical tools. Respondents rated the actual procurement stage as "Fully Implemented," while the pre-procurement (procurement planning) and post-procurement (procurement monitoring) stages were rated as "Moderately Implemented." Differences in perceptions were found based on age and agency affiliation for the pre-procurement (procurement planning) and actual procurement stages and on age, agency affiliation, and roles for the post-procurement (procurement monitoring) stage. The findings recommend creating an action plan focused on establishing a uniform procurement policy, adopting technological improvements, strengthening procurement monitoring, and professionalizing and evaluating procurement personnel to ensure procurement efficiency